Leaching of Atrazine in Commercial and Xerogel Formulations in Oxisol Using Bioassay and Chromatographic Methods - Marchesan,E.D. (2015)
Mobility of atrazine in soil has contributed to the detection of levels above the legal limit in surface water and groundwater in Europe and the United States. The use of new formulations can reduce or minimize the impacts caused by the intensive use of this herbicide in Brazil, mainly in regions with higher agricultural intensification. The objective of this study was to compare the leaching of a commercial formulation of atrazine (WG) with a controlled release formulation (xerogel) using bioassay and chromatographic methods of analysis. The experiment was a split plot randomized block design with four replications, in a (2 x 6) + 1 arrangement. The main formulations of atrazine (WG and xerogel) were allocated in the plots, and the herbicide concentrations (0, 3200, 3600, 4200, 5400 and 8000 g ha-1), in the subplots. Leaching was determined comparatively by using bioassays with oat and chromatographic analysis. The results showed a greater concentration of the herbicide in the topsoil (0-4 cm) in the treatment with the xerogel formulation in comparison with the commercial formulation, which contradicts the results obtained with bioassays, probably because the amount of herbicide available for uptake by plants in the xerogel formulation is less than that available in the WG formulation.